Design zigzag edge of S shape slot antenna by using SIW technology for 5G application - Alaa Abd Ali Hadi; Essam Hamoodi Ahmed; Baydaa Hadi Saoudi; Yaqdhan Mahmood Hussein; Tabarek Alwan Tuib (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
This study offers a 5G substrate integrated waveguide (SIW) antenna with vertical S zigzag shape slot. The suggested antenna's radiating patch depends on the shape of the slot. Two types of slots have been used, straight and zigzag S shape slot with vertical and horizontal direction, slots are etched on the patch to increase the antenna's overall bandwidth and gain. The suggested straight and zigzag SIW S slot antennas both resonate at 28 GHz, and the overall structure size is 7.10×14.93 mm. The presented design could achieve high gain, efficiency, and minimal losses, which are all important concerns. The presented antenna may produce a gain of 9.48 dB, a 95% efficiency, and a wider bandwidth of no less than 3.25 GHz at 28 GHz.